Cancer diagnosis in patients with heart failure: epidemiology, clinical implications and gaps in knowledge. (21st February 2018) - Ameri, Pietro; Canepa, Marco; Anker, Markus S.; Belenkov, Yury; Bergler‐Klein, Jutta; Cohen‐Solal, Alain; Farmakis, Dimitrios; López‐Fernández, Teresa; Lainscak, Mitja; Pudil, Radek; Ruschitska, Frank; Seferovic, Petar; et al.
Abstract : Cancer and heart failure (HF) are common medical conditions with a steadily rising prevalence in industrialized countries, particularly in the elderly, and they both potentially carry a poor prognosis. A new diagnosis of malignancy in subjects with pre‐existing HF is not infrequent, and challenges HF specialists as well as oncologists with complex questions relating to both HF and cancer management. An increased incidence of cancer in patients with established HF has also been suggested. This review paper summarizes the epidemiology and the prognostic implications of cancer occurrence in HF, the impact of pre‐existing HF on cancer treatment decisions and the impact of cancer on HF therapeutic options, while providing some practical suggestions regarding patient care and highlighting gaps in knowledge.